Metastable States in Amorphous Chalcogenide Semiconductors - Mikla, Victor I.; Mikla, Victor V. (Springer Series in Materials Science, 2010)
This book addresses an interesting and technologically important class of materials, the amorphous chalcogenide semiconductors. Experimental results on the structural and electronic metastable states in Se-rich chalcogenides are presented. Special attention is paid to the states in the mobility gap and their sensitivity to various factors such as irradiation, annealing and composition. Photoinduced changes of structure and physical properties are also considered and structural transformation at photocrystallization is studied in detail. Finally, the authors discuss potential applications of the observed effects in xerography, digital radiography and for optical data storage.